Exploring the chicken embryo as a possible model for studying Listeria monocytogenes pathogenicity - Gripenland, Jonas; Andersson, Christopher; Johansson, Jörgen (Frontiers in Cellular and Infection Microbiology, 2014)
Listeria monocytogenes is a bacterial pathogen capable of causing severe infections in humans, often with fatal outcomes. Many different animal models exist to study L. monocytogenes pathogenicity, and we have investigated the chicken embryo as an infection model: What are the benefits and possible drawbacks? We have compared a defined wild-type strain with its isogenic strains lacking well-characterized virulence factors. Our results show that wild-type L. monocytogenes, already at a relatively low infection dose (~5 x 102 cfu), caused death of the chicken embryo within 36 hours, in contrast to strains lacking the main transcriptional activator of virulence, PrfA, or the cytolysin LLO. Surprisingly, strains lacking the major adhesins InlA and InlB caused similar mortality as the wild-type strain. In conclusion, our results suggest that the chicken embryo is a practical model to study L. monocytogenes infections, especially when analyzing alternative virulence pathways independent of the InlA and InlB adhesins. However, the route of infection might be different from a human infection. The chicken embryo model and other Listeria infection models are discussed.